PENGARUH PEOPLE, PROCESS, DAN PHYSICAL EVIDENCE TERHADAP KEPUASAN ATAS PELAYANAN PADA PERBANKAN SYARIAH DI KOTA PADANG - SIGIT SANJAYA; NILA PRATIWI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2018)
This study aims to analyze: 1) the effect of people on the satisfaction of services in Islamic banking in Padang city 2) the effect of process on satisfaction of services in Islamic banking in Padang city 3) the effect of physical evidence on satisfaction of services in Islamic banking in Padang city. This study classified as descriptive causative research. The population in this study are custome in Islamic banking in Padang city. Determination of the number of samples using the Hair’s method. The distribution of questionnaires used accidental sampling techniques. Data were collected through questionnaires using a Likert scale and data analysis using PLS SEM. The results of this study indicate that: 1) there is a significant positive effect between people on satisfaction of service to Islamic banking in the city of Padang. 2) there is no significant effect between the process on satisfaction of serviceso in Islamic banking in Padang city 3) there is no significant effect between physical evidence on satisfaction of services in Islamic banking in Padang city.